Intestinal and Renal Effects of Low-Volume Phosphate and Sulfate Cathartic Solutions Designed for Cleansing the Colon: Pathophysiological Studies in Five Normal Subjects - Patel, Viralkumar; Nicar, Michael; Emmett, Michael; Asplin, John; Maguire, John A; Santa Ana, Carol A; Fordtran, John S (The American journal of gastroenterology, 2009)
Ingestion of a concentrated low-volume phosphate solution produces copious diarrhea, which cleanses the colon, but it occasionally causes renal failure due to calcium phosphate precipitation in renal tubules. We hypothesized that a concentrated low-volume sulfate solution would be an equally effective cathartic, and that urine produced after sulfate would have less tendency to precipitate calcium salts than urine produced after phosphate. Hydrated subjects ingested 75 ml of phosphosoda or an equimolar dose of sulfate salts in a small volume of solution. Four liters of PEG (polyethylene glycol) lavage solution was the control. All solutions were administered in split doses, 10 h apart. Propensity of urine to precipitate at pH 6.4 (the pH of renal tubular fluid) was assessed by determining the minimal calcium concentration that caused precipitation. Average diarrheal stool weight was 2,004 g after phosphate, 2,854 g after sulfate, and 3,021 g after PEG (P<0.001). Average calcium concentration (in mg/dl) required to induce urine precipitation at pH 6.4 was 43 after PEG, 10 after PO(4), and 187 after SO(4) (P=0.009). (i) In equimolar doses, sulfate produced 42% more diarrheal stool weight than phosphate. (ii) Phosphate increased the propensity for calcium salt precipitation in urine at pH 6.4, whereas sulfate did not. (iii) These results suggest that a hypertonic low-volume sulfate solution would be an effective cathartic for colon cleansing and that sulfate-induced catharsis would be less likely than phosphate catharsis to produce calcium salt deposition in renal tubules.